Food Allergens Best Practices for Assessing, Managing and Communicating the Risks - Fu, Tong-Jen.; Jackson, Lauren S.; Krishnamurthy, Kathiravan; Bedale, Wendy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume identifies gaps in the assessment, management, and communication of food allergen risks. Chapters showcase best practices in managing allergen risks at various stages of the food chain, including during food manufacture/processing; during food preparation in food service, retail food establishments, and in the home; and at the point of consumption. The authors highlight key legislative initiatives that are in various stages of development and implementation at the federal, state and community levels. Finally, the volume includes recommendations for ways to build and strengthen education and outreach efforts at the food industry, government, institutional, and community levels. Chapters come from an array of experts, including researchers and key stakeholders from government, the food industry, retail/food service groups, and consumer groups. The information presented will facilitate the development of educational materials and allergen management training programs for food production and service staff, extension specialists, and government inspectors. Consumers and other food safety professionals will also benefit from information on food allergen control measures that have been put in place across the food chain.
Chapter1. Best Practices for Assessing, Managing and Communicating Food Allergens Risks: An Introduction -- Chapter2. A Review of the Distribution and Costs of Food Allergy -- Chapter3. Current U.S. State Legislation Related to Food Allergen Management -- Chapter4. Current Trends in Food Allergy Advocacy: Prevention, Preparedness, and Epinephrine Availability -- Chapter5. Food Allergen Recalls - The Past as Prologue -- Chapter6. Allergen Management: Ensuring What is in the Product is on the Package -- Chapter7. Allergen Management in Food Processing Operations: Keeping What Is Not on the Package Out of the Product -- Chapter8. Allergen Cleaning Best Practices -- Chapter9. Survey: Food Allergen Awareness in the Restaurant and Foodservice Industry -- Chapter10. Allergen Management in Food Service -- Chapter11. The 4 Key Elements to Feeding Diners with Allergies: Culture, Education, Caring & Orchestration -- Chapter12. Managing Food Allergens in Retail Quick-Service Restaurants -- Chapter13. FoodAllergen Online Training: An Example of Extension's Educational Role -- Chapter14. Allergen Control at Home -- Chapter15. Allergen Control for College and University Dining Service.
Keywords: Food -- Microbiology; Food science; Public health; Food Microbiology; Food Science; Public Health